Blood pact - Hagberg, David (Hagberg, David. Kirk McGarvey adventures., 2014)
"A large portion of the fabulous treasure originally stolen by conquistadors of the eighteenth century was buried in the desert of southern New Mexico by Spanish monks. Jacob Ambli, a Catholic priest, was sent as a spy on a Spanish military mission to find seven caches left for the Church. He kept a diary showing the locations, but was murdered trying to get back to Rome, and the journal was lost. Now, a century and a half later, the diary has come to light, and the Spanish government, Cuban intelligence agency, and the Catholic Church are racing to be the first to claim it. Kirk McGarvey is approached by a shadowy organization that wants to beat all of them to the book--the Voltaire Society, a mysterious group whose purpose is shrouded in the history of the United States. The chase takes Mac from Washington to Malta and finally to Seville, where he comes up against a fifth foe--one of the most ruthless assassins he has ever confronted--who has made a blood pact with the agents of the devil to find the lost treasure no matter what the cost"--